2017
DOI: 10.1016/j.pan.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Academic Pancreas Centers of Excellence: Guidance from a multidisciplinary chronic pancreatitis working group at PancreasFest

Abstract: Chronic pancreatitis (CP) is a progressive inflammatory disease, which leads to loss of pancreatic function and other disease-related morbidities. A group of academic physicians and scientists developed comprehensive guidance statements regarding the management of CP that include its epidemiology, diagnosis, medical treatment, surgical treatment, and screening. The statements were developed through literature review, deliberation, and consensus opinion. These statements were ultimately used to develop a concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…DM onset generally develops many years following disease onset, and may ultimately affect up to 80% of patients during their lifetime 45 . Due to the high prevalence of CP-DM annual screening for DM is recommended 46,47 . A recent study of 1,171 subjects with CP demonstrated that DM was more likely to occur in subjects who were older, obese, male sex, black race, or with a family history of DM, while factors independently associated with DM included both obesity and the presence of exocrine pancreatic insufficiency (EPI) 43 .…”
Section: Chronic Pancreatitis-related Diabetes Mellitusmentioning
confidence: 99%
“…DM onset generally develops many years following disease onset, and may ultimately affect up to 80% of patients during their lifetime 45 . Due to the high prevalence of CP-DM annual screening for DM is recommended 46,47 . A recent study of 1,171 subjects with CP demonstrated that DM was more likely to occur in subjects who were older, obese, male sex, black race, or with a family history of DM, while factors independently associated with DM included both obesity and the presence of exocrine pancreatic insufficiency (EPI) 43 .…”
Section: Chronic Pancreatitis-related Diabetes Mellitusmentioning
confidence: 99%
“…Pancreatitis is an inflammatory disease of the pancreas and divided into acute and chronic pancreatitis. Chronic pancreatitis (CP) is characterized by irreversible inflammatory disorders that leading to fibrotic destruction of pancreatic parenchyma, endocrine, and exocrine dysfunction ( Sheth et al, 2017 ). CP develops due to repeated episodes of acute pancreatitis (AP) resulting in the activation of pancreatic stellate cells (PSCs); thus fibrosis ( Beyer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…DM usually occurs several years after the onset of the disease and can eventually affect up to 80% of patients over their lifespan [69]. Due to the high prevalence of CP-DM, annual screening for DM is recommended [70,71]. In a recent study of participants with CP, DM was more likely to occur in participants who were older, obese, male, black race, or had a family history of DM and factors independently associated with DM included both obesity and the presence of exocrine pancreatic insufficiency [72].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In other gastrointestinal conditions, such as celiac disease, cholestatic liver disease, and inflammatory bowel disease, baseline screening with a DEXA scan has been widely adopted. That is why, baseline screening with DEXA in CP is reasonable considering that CP has higher odds of fractures compared with other gastrointestinal conditions [67,71].…”
Section: Treatment Of Metabolic Bone Disordermentioning
confidence: 99%
See 1 more Smart Citation